Motivation as Mediation Variable in the Effect of Knowledge Level and Socio-economic Status to Participation of PUS (Couples of Reproductive Age) - Nurhayati, Ermy; Sutarto, Joko; Mulyono, Sungkowo Edy (Journal of Nonformal Education, 2018)
The aims of this study were: (a) to analyze the direct effect of knowledge on the motivation of Couple of Reproductive Age, (b) to analyze the direct effect of socio-economic status on Couple of Reproductive Age motivation, (c) to analyze the direct effect of knowledge on Couple of Reproductive Age participation, (d) to analyze the direct effect of socio-economic status on Couple of Reproductive Age participation, (e) Analyzing the indirect effect of knowledge on the participation of PUS through motivation, (f) Analyzing the indirect effect of socioeconomic status on the participation of PUS through motivation. The research approach was quantitative. Data collecting technique was done by observation and questioner. The Couple of Reproductive Age population on the age of 30-45 years old in Juwiring is 3.086 and the number of sample was 248 respondents. The data analyzed by using Path Analysis test. The results of the study were: (a) There was significant effect of knowledge level to the motivation in Family Planning (26.10%), (b) There was significant effect of socio-economic status to the motivation in Family Planning (24,10%), (c) There was significant effect of knowledge level on the participation of PUS in Family Planning (67%), (d) There was significant effect between socioeconomic status on PUS participation in Family Planning (19.60%), (e) Motivation was able to mediate the Effect of Knowledge Level on PUS Participation in Family Planning, (f) Motivation was able to mediate the effect of Socio-economic Status to Participation of PUS in Family Planning.